2022
DOI: 10.1186/s40168-021-01211-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of fiber utilization in the rumen of dairy cows based on metagenome-assembled genomes and single-cell RNA sequencing

Abstract: Background Dairy cows utilize human-inedible, low-value plant biomass to produce milk, a low-cost product with rich nutrients and high proteins. This process largely relies on rumen microbes that ferment lignocellulose and cellulose to produce volatile fatty acids (VFAs). The VFAs are absorbed and partly metabolized by the stratified squamous rumen epithelium, which is mediated by diverse cell types. Here, we applied a metagenomic binning approach to explore the individual microbes involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 80 publications
3
31
0
Order By: Relevance
“…CCSER1 was reported to be involved in the cell division defect with a potential impact on microbiome components in human colorectal cancer ( 28 ). The expression of this gene has been found in rumen epithelial tissues of dairy and beef cattle based on their transcriptome profiles ( 29 , 30 ), suggesting that this SNP may potentially influence the rumen microbiota by affecting the cell functions of the rumen epithelial wall. Of the heritable bacteria-associated SNPs, five are also associated with the variation of lactation performance.…”
Section: Discussionmentioning
confidence: 99%
“…CCSER1 was reported to be involved in the cell division defect with a potential impact on microbiome components in human colorectal cancer ( 28 ). The expression of this gene has been found in rumen epithelial tissues of dairy and beef cattle based on their transcriptome profiles ( 29 , 30 ), suggesting that this SNP may potentially influence the rumen microbiota by affecting the cell functions of the rumen epithelial wall. Of the heritable bacteria-associated SNPs, five are also associated with the variation of lactation performance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, VFA, acetate, propionate and valerate were also elevated with S30 and S40, which may be attributed to the enrichment of Prevotella , which was the core genus of Bacteroidetes. The functions of this microbe include the fermentation of carbohydrates, the utilization of nitrogenous substances, and the biotransformation of bile acids and other steroids; the main by-products of anaerobic respiration are acetate, isovalerate, and succinate, which are closely related to VFA biosynthesis [ 39 , 40 ]. Moreover, propionate is a major substrate of gluconeogenesis, and a recent study also showed that it is closely related to ruminal N metabolism [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, our group has determined temporal changes in several nutrient transporters and metabolic genes in ruminal epithelium around parturition and, in some cases [e.g., HMGCS2 (rate-limiting ketogenic enzyme), SLC16A1 (VFA transporter)], mRNA abundance is stable from −14 through 10 DIM, after which upregulation occurs by d 28 (Minuti et al, 2015). Recent studies with lactating cows have underscored the complexity of the ruminal epithelium, highlighting the existence of cell subtypes that seem to be crucial for VFA uptake and metabolism (Xue et al, 2022). Among these findings, an IGFBP5+ cg-like spinous cell population is unique because of its high expression of SLC16A1 and the cation-HCO 3 − exchanger SLC4A9.…”
Section: Discussionmentioning
confidence: 99%